Analysis of phase transformation and blanking accuracy of B1500HS steel during hot blanking. (2017) - Hou, Hongli; Li, Huiping; He, Lianfang; Tang, Bingtao
Abstract: Hot blanking process not only produces a variety of fine blanking parts have comprehensive mechanical properties, but also solve the difficulties in the piercing and trimming of press-hardened parts. To explore the optimal hot blanking process and investigate the effects of some technological parameters on the phase-transformation and dimensional accuracy of the parts, several different blanking temperatures (450 °C, 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C, and 800 °C) and die clearances (25%, 20%, 18%, 16%, 14%, 12%, 10%, and 8%) were used in the hot blanking of B1500HS steel. The results show that the diameters of blanked parts increase with the decrease of die clearance at the same blanking temperature. When the die clearance is constant, the dimensional deviation of diameter for the blanked parts shows the trend of "positive growth‒negative growth‒positive growth" with the decrease of blanking temperature. The higher dimensional accuracy of blanked parts can be attained at the blanking temperatures 450–500 °C, 600–650 °C, or 750–800 °C. The microstructure of blanked parts is complete martensite at the blanking temperatures 650–800 °C, the microhardnesses of parts are approximately 550 HV.